1986
DOI: 10.1002/j.1460-2075.1986.tb04634.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific DNA binding of the progesterone receptor to the uteroglobin gene: effects of hormone, antihormone and receptor phosphorylation.

Abstract: The effects of ligand binding and receptor phosphorylation on the interaction of progesterone receptor with specific DNA sequences in the uteroglobin gene were studied by nitro‐cellulose filter binding and DNase I footprinting. High affinity sites were mapped upstream from the transcription start and in the first intron. They contained a common TGTTCACT sequence. These sites were occupied with similar affinity by the receptor, either in its free state, or complexed with the hormone or an antagonist (RU486); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
2

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(71 citation statements)
references
References 38 publications
6
63
2
Order By: Relevance
“…BIOL. progesterone receptor on other genes (1,14,29). On the VTG II gene fragment, the DNase I-hypersensitive sites were localized at positions -620 and -612 to -615 on the lower DNA strand (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…BIOL. progesterone receptor on other genes (1,14,29). On the VTG II gene fragment, the DNase I-hypersensitive sites were localized at positions -620 and -612 to -615 on the lower DNA strand (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In vitro receptor-DNA binding studies have shown that this hexanucleotide and neighboring sequences on the VTG II gene are bound by the glucocorticoid receptor (26) and could also possibly be recognized by the androgen receptor (6). The hexanucleotide motif is also part of the recognition sequence of the progesterone receptor (1,14,29).The close proximity of the hexanucleotide motif to the ERED on the VTG II gene prompted us to study the functional interaction of these two elements with progestin, androgens, and estradiol in transfection experiments in T47D cells that contain receptors for all three steroid hormones (6). In this communication we present the results of these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The glucocorticoid and progesterone receptors bind to similar sequences within these fragments, suggesting that the binding sites may be closely related, but distinct (5, 6). Both types of receptors also bind to partially overlapping sequences in the rabbit uteroglobin gene (7,8). These sequences, however, have not been functionally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The potential cis-acting elements for progesterone activation of the gene have only been mapped in DNA binding experiments in vitro. Progesterone receptor-binding sites have been assigned to the first intron of the gene (15), as well as to a region between 2.4 and 2.7 kb upstream of the transcription start site, where two clusters of three imperfect binding sites for glucocorticoid and progesterone receptors have been found (16,17). The relevance of these upstream receptor-binding sites was supported by the appearance of adjacent progesterone inducible DNase I-hypersensitive sites in chromatin of isolated nuclei from endometrial epithelium (17).…”
mentioning
confidence: 99%